Electronic and Structural Property Comparison of Iridium-Based OER Nanocatalysts Enabled by Operando Ir L3-Edge X-ray Absorption Spectroscopy - van der Merwe, Marianne; Wibowo, Romualdus Enggar; Jimenez, Catalina E.; Escudero, Carlos; Agostini, Giovanni; Bär, Marcus; Garcia-Diez, Raul (ACS Catalysis, 2024)
In this study, we investigate the electronic and structural behavior of a newly developed and of a commercially available Ir-based oxygen evolution reaction (OER) catalyst under relevant conditions employing an operando Ir L3-edge X-ray absorption near-edge structure and extended X-ray absorption fine structure approach. The newly developed Kopernikus P2X amorphous IrOx/TiO2 catalyst is compared to the current commercial benchmark catalyst: crystalline IrO2/TiO2, Umicore Elyst. Analysis of the redox behavior of the catalysts shows distinct electronic differences between the amorphous and crystalline oxides, with the former exhibiting significant reversible electronic transformations. Employing an equivalent charge transfer approach following Faraday’s law of electrolysis, we study the behavior of the catalysts under equivalent OER conditions (chronopotentiometric steps), as opposed to the conventional chronoamperometric approach. This enables the derivation of property-structure relationships under equivalent OER conditions for materials exhibiting distinctly different activities. The P2X IrOx/TiO2 catalyst undergoes substantial electronic structure changes, with larger reduction in the Ir-O bond lengths compared to that of the commercial benchmark catalyst. The correlation between electronic states and local geometric information highlights diverse OER pathways, suggesting that the newly developed P2X IrOx/TiO2 catalyst and the benchmark IrO2/TiO2 commercial catalyst follow mechanisms akin to those of amorphous iridium oxide (am-IrOx) and rutile-IrO2, respectively. These results shed light on the intrinsic activities of different iridium oxide-based catalysts and provide crucial insights for enhancing their performances in proton exchange membrane water electrolyzers.
CRIS-Team Scopus Importer:2024-11-15
Keywords: chronopotentiometry; equivalent charge transfer; Ir-based catalyst; operando Ir L; oxygen evolution reaction